Experimental investigation of seawater volume effect on the performance of a corrugated-V absorber solar still - Arfan Halim; Ilmawan Suryapradana; Adit S; Abraham P (Jurnal Polimesin, 2026)
Limited access to clean water in coastal and remote areas has spurred the development of simple desalination technologies powered by renewable energy. This study analyzes the effect of seawater volume variation on the performance of a solar distillation system employing a corrugated-V absorber plate at a 40° tilt angle. The absorber plate was fabricated from aluminum and coated with matte black paint to enhance solar radiation absorption. Experimental tests were conducted under natural solar radiation conditions with seawater volumes of 5L, 6L, and 7L from 09:00 to 16:00 local time. The observed parameters included estimated solar radiation intensity, absorber plate temperature, basin water temperature, system efficiency, and condensate production. The results indicate that seawater volume significantly influences the thermal characteristics and productivity of the solar still. Among the tested variations, the 6L volume showed the best performance, achieving an average efficiency of 40.54% and a maximum condensate yield of 0.36L. At 5L, the available thermal energy was not effectively utilized, whereas at 7L, the increased water mass resulted in slower heating and evaporation rates. These findings demonstrate that appropriate selection of seawater volume plays an important role in enhancing the performance of solar distillation systems equipped with corrugated-V absorber plates under real outdoor operating conditions.